PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PERSETUBUHAN OLEH ANGGOTA POLRI YANG TIDAK MENDAPATKAN GANTI RUGI: Legal Protection For Victims Of Sexual Intercourse Crimes Committed By Police Officers Who Do Not Receive Compensation - Sony Fati Crisitan Gulo; Ermania Widjajanti (Reformasi Hukum Trisakti, 2025)
Protection is all efforts to fulfill rights and provide assistance to provide a sense of security to Witnesses and/or Victims. This causes physical and psychological harm to the victim. As happened to the victim of sexual intercourse committed by the perpetrator who was a member of the National Police in Banjarmasin. Therefore, the formulation of the problem of this study is: 1. How are the legal protection efforts for victims of sexual intercourse by members of the National Police who do not receive compensation? 2. How are the rights of victims of sexual intercourse by members of the National Police who do not receive compensation fulfilled? The research method used by the author is normative juridical which includes research on legal principles, victims can apply for restitution in the form of compensation, victims have the right to receive protection from LPSK. Research results and conclusions of the study show that victims must receive protection through restitution and assistance from LPSK. The rights of victims, including medical costs and psychosocial rehabilitation as regulated in Law No. 31 of 2014 and Perma No. 1 of 2022, with legal mechanisms that ensure the fulfillment of these rights.